Application of MDS Codes in Solving Problem of Distributing Exam Questions - Ricky Aditya (Pattimura Proceeding, 2023)
In online learning, giving an objective assessment is quite tricky task. Most of exams in online learning are done as take-home exams. Unlike in face-to-face onsite class, in which the students can be observed directly when doing the exam, in online class the students have chance to cheat and work together to gain unfair advantage. To tackle this, the teachers need to modify the exam format. One possible solution is to create some variations of exam questions and distribute them to the students such that they do not get the same set of questions. However, we cannot create too many variations since it would make the grading process more difficult for the teacher. Thus, we need to find an optimal way to do so. In this article, we will discuss how Maximum Separable Distance (MDS) Codes in coding theory can be applied to provide a solution for this problem. Moreover, distribution patterns for class of size 27, 64 and 125 students will also be presented.